Hubungan Dukungan Keluarga Dengan Kemampuan Mobilisasi Dini Pada Pasien Post Operasi Sectio Metode ERACS - Tanti Nuriyanti; Nurul Ainul Shifa; Nur Eni Lestari (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Electronic Based on several studies, the number of caesarean sections continues to increase and with widespread news regarding the use of the ERACS method in the caesarean section process, which is believed to optimize the mother's health and comfort both before, during and after undergoing caesarean surgery, so that mobility and the birth recovery process can be improved. fast. Early mobilization is one of a series of methods and according to theory there are several things that influence the implementation of early mobilization after surgery, one of which is the impact of support from family members. This study aims to determine the relationship between family support and the ability to mobilize early in post-SC surgery patients with the ERACS method at Azra Hospital Bogor in 2023. This type of research is observational with a cross sectional design. The research sample was 45 post-caesarean section mothers at Azra Bogor Hospital. The research results showed that the majority of 35 respondents (77.8%) had good family support, there were 37 respondents (82.2%) who had early mobilization abilities, of which 10 respondents (22.25%) had poor family support There were 8 people (17.7%) who still assisted with early mobilization. With the Chi Square analysis test, the p-value = 0.001 was obtained, so there is a significant relationship between family support and early mobilization for post-SC mothers using the ERACS method at Azra Bogor Hospital in 2023. Conclusion, the better family support, the more the patient tends to mobilize, and conversely, if the family support is not good, the ability to early mobilize tend to improve